Feasibility of a Pharmabuddy Care Service for patients with Parkinson’s disease - C. C. M. Stuijt; F. Karapinar-Çarkit; C. van de Steeg – van Gompel; T. van Laar; B. J. F. van den Bemt; M. Heringa (BMC Health Services Research)
Abstract Background Pharmaceutical care for patients with Parkinson’s disease (PD) is complex. Specialized pharmaceutical care provided by a dedicated pharmacy team member (pharmabuddy) for these patients may reduce medication-related problems. The feasibility of this service for PD patients is unknown. Objective To evaluate the feasibility of a Pharmabuddy Care Service (PCS) for PD patients in primary care pharmacies. Methods Pharmabuddies who offered PCS were invited to fill in a questionnaire to evaluate the feasibility of PCS. Patients received a patient questionnaire and were invited for an interview. Patient records provided information on medication-related problems and interventions. Feasibility was evaluated conform four domains of Bowen’s Framework. First, acceptability included patients’ satisfaction ratings and experiences, Pharmabuddy impression on start and continuation of the service. Second, demand included use by patients and provision by pharmabuddies. Third, implementation/practicality: implementation indicators and barriers and facilitators from patient- and pharmabuddy perspective and fourth limited efficacy: effect of the PCS on PD symptoms, medication related problems identified and interventions from patient records. Results Twenty-three (59%) patients completed the questionnaire, 9 were interviewed, 12 (67%) pharmabuddies responded. Acceptability was high among patients (mean 9.5 (SD 1.3) out of 10), 6 (50%) pharmacies (still) provided PCS. Demand: 56% of patients had 1–2 contact moments, 28% two or more. Ten pharmacies provided up to 14 patients per pharmacy with PCS, one up to 24. Implementation/practicality: important barriers were time constraints and perception of other healthcare professionals. Positive reactions from patients encouraged pharmabuddies to carry out their PCS-activities. Patients were positive about pharmabuddy’s listening competency while knowledge could be improved. Limited efficacy: from patient records, 89 interventions were made in response to 93 (median 3 per patient (range 1–16)) medication related problems or questions, with 20 (87%) patients reporting a positive effect from their interaction with a pharmabuddy. Conclusion This study shows PCS is highly appreciated by responding patients and can be feasible for primary care pharmacies. Several implementation issues are still present. Future studies should focus on quantifiable effects of PCS services as well as resource and perception hurdles.